The degree of servant leadership practice among the heads of administrative departments at the University of Palestine and ways to improve it (Palestine Technical College Journal for Research and Studies, 2022)
The study aimed to identify the degree of servant leadership practice among the heads of administrative departments at the University of Palestine from the point of view of its employees, and to reveal whether there were statistically significant differences at the significance level (α 0.05) between the average degrees of estimation of the members of the sample to the degree of practice of the heads of administrative departments at the University of Palestine. For servant leadership is attributed to the variables: (gender, years of service, educational qualification, specialization), In order to reach procedural proposals to improve the degree of servant leadership practice among the heads of administrative departments at the University of Palestine from the point of view of its employees, and by using the descriptive/surveying  and referring to the related literature, a questionnaire was build consisting of (40) items distributed on (6) fields: (Conceptual skills, employee empowerment, trust, concern for workers and their service, commitment to community development, and personal values), and after verifying their validity and stability, they were applied to a sample of (97) male and female employees. The study found that the degree of servant leadership practice among the heads of the administrative departments was "medium", and there were no statistically significant differences at the significance level (α 0.05) between the mean scores of the sample members' estimation of the degree of servant leadership practice by the heads of administrative departments at the University of Palestine due to the study variables. The results showed that the most important procedural proposals to improve the degree of servant leadership practice among the heads of administrative departments at the University of Palestine from the point of view of its employees, is to hold more qualification courses for the heads of administrative departments to confirm the concept of servant leadership and its applied practices in the field of administrative work.
Keywords: servant leadership; administrative departments; University of Palestine